HTERT-Immortalized Bone Mesenchymal Stromal Cells Expressing Rat Galanin via a Single Tetracycline-Inducible Lentivirus System. (11th May 2017) - An, Ke; Liu, Hui-ping; Zhong, Xiao-long; Deng, David Y. B.; Zhang, Jing-jun; Liu, Zhi-heng
Abstract : The use of human telomerase reverse transcriptase-immortalized bone marrow mesenchymal stromal cells (hTERT-BMSCs) as vehicles to deliver antinociceptive galanin (GAL) molecules into pain-processing centers represents a novel cell therapy strategy for pain management. Here, an hTERT-BMSCs/Tet-on/GAL cell line was constructed using a single Tet-on-inducible lentivirus system, and subsequent experiments demonstrated that the secretion of rat GAL from hTERT-BMSCs/Tet-on/GAL was switched on and off under the control of an inducer in a dose-dependent manner. The construction of this cell line is the first promising step in the regulation of GAL secretion from hTERT-immortalized BMSCs, and the potential application of this system may provide a stem cell-based research platform for pain.